Vida Saludable: Juego de letras para cambiar su estilo de vida - Valerie Weyenberg; Karla P. Shelnutt (EDIS)
FCS8894Span, a 1-page handout by Valerie Weyenberg and Karla P. Shelnutt, is the Spanish-language version of Healthy Living: Change Your Lifestyle Word Scramble (FCS8894). It provides an activity to familiarize program participants with lifestyle changes that can help prevent high blood pressure. Published by the UF Department of Family Youth and Community Sciences, April 2010.